Hydrophilic Hydroxyapatite Cement Cranioplasty: Preventing Cerebrospinal Fluid Leaks and Wound Complications in Translabyrinthine Acoustic Neuroma Surgery. (2nd September 2014) - Jackson, Neal; Spear, Samuel A.; Mehta, Rahul; Ying, Yu‐Lan Mary; Scrantz, Kelly; Culicchia, Frank; Arriaga, Moises A.
Abstract : Objectives: (1) Examine the efficacy of quick‐setting, hydrophilic formulation of hydroxyapatite cement (HAC) used in cranioplasty for the prevention of cerebrospinal fluid (CSF) leaks and long‐term wound complications following translabyrinthine acoustic neuroma (TLAN) surgery. (2) Review evolution of HAC cranioplasty. Methods: Retrospective case review from 2006 to 2013 in atertiary referral center. Consecutive patients undergoing translabyrinthine approach for acoustic neuroma tumors were operated on by the senior author. Intervention: Therapeutic: Cranioplasty combining a medial abdominal fat graft with hydrophilic hydroxyapatite cement filling the mastoid. Main outcome measures: Incidence of cerebrospinal fluid (CSF) leaks and any wound complications. Results: Forty‐four patients met inclusion criteria. There were no CSF leaks or other wound complications in this series. Conclusions: Hydrophilic HAC appears to be safe and efficacious for cranioplasty following translabyrinthine acoustic neuroma surgery.